Contribution of Character Education in Madrasah Ibtidaiyah Teacher Education Curriculum - Abdillah, Muhammad; Munawwaroh , Siti (ELEMENTARY : Journal of Primary Education, 2024)
This research explores the contribution of character education in the Madrasah Ibtidaiyah teacher education curriculum and its impact on the quality of education in these institutions. Character education is an important component in shaping students' morals and attitudes in Madrasah Ibtidaiyah, which is an educational institution that integrates aspects of general science and religion. This article uses the literature review method to examine various studies and related sources that discuss the implementation of character education in the teacher education curriculum. The results show that the integration of character education in the teacher education curriculum not only enriches teachers' pedagogical competencies but also enhances their ability to shape students' positive character. Effective character education helps teachers in developing teaching methods that not only focus on academic aspects, but also on shaping students' moral and social values. However, challenges such as lack of adequate training and limited resources often hinder optimal implementation. This study recommends the need for strengthening character education training for prospective teachers, as well as providing better support from education institutions, to ensure that character education can be effectively implemented in the curriculum and have a significant positive impact on the quality of education in Madrasah Ibtidaiyah.